2014
DOI: 10.15446/abc.v20n2.42713
|View full text |Cite
|
Sign up to set email alerts
|

In vitro DISSOLUTION OF ACIDULATED ROCK PHOSPHATE BY PHOSPHATE SOLUBILIZING MICROORGANISMS

Abstract: The low availability of phosphorus (P) in the soil and the high cost of P fertilization are factors that limit agricultural productivity. A biotechnological alternative for to handle this problem is to use soil microorganisms capable of dissolving rock phosphate (RP), thus improving its effectiveness as a P fertilizer. This study was carried out with the objective of determining the effectiveness of Aspergillus niger -As-, Penicillium sp. -Pn-, Bacillus sp -B-. and an unidentified actinomycete -At-in the in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
(40 reference statements)
0
1
1
Order By: Relevance
“…In both the P and K solubilization tests in the liquid medium, a decrease in pH was observed, however, the yeasts with the lowest pH did not show a direct relationship with the increase in PS and KS values, this results do not agree with what was reported by Moreno Quevedo et al (2015) where cultures inoculated with Aspergillus niger indicated the reduction in pH as an indicator of the solubilization capacity of P, in their studies the values of pH 3.58 were those who obtained a higher concentration of soluble phosphorus (42.3 mg L -1 ); and Bagyalakshmi et al (2017) achieved the highest solubilization of K (41.91 mg L -1 ) with Pseudomonas nitroreducens when reducing the pH to values of 4.5 being the lowest of all their study. According to reports found, the acidification of the medium occurs as a result of the synthesis of organic acids such as oxalic, formic, citric, malic, propionic, tartaric acid, among others (Kumar et al, 2016;Xiao et al, 2013), this reduction in pH induces the ability to release K and P from minerals to bring them to their available solution form (Teotia et al, 2016).…”
Section: Discussioncontrasting
confidence: 86%
“…In both the P and K solubilization tests in the liquid medium, a decrease in pH was observed, however, the yeasts with the lowest pH did not show a direct relationship with the increase in PS and KS values, this results do not agree with what was reported by Moreno Quevedo et al (2015) where cultures inoculated with Aspergillus niger indicated the reduction in pH as an indicator of the solubilization capacity of P, in their studies the values of pH 3.58 were those who obtained a higher concentration of soluble phosphorus (42.3 mg L -1 ); and Bagyalakshmi et al (2017) achieved the highest solubilization of K (41.91 mg L -1 ) with Pseudomonas nitroreducens when reducing the pH to values of 4.5 being the lowest of all their study. According to reports found, the acidification of the medium occurs as a result of the synthesis of organic acids such as oxalic, formic, citric, malic, propionic, tartaric acid, among others (Kumar et al, 2016;Xiao et al, 2013), this reduction in pH induces the ability to release K and P from minerals to bring them to their available solution form (Teotia et al, 2016).…”
Section: Discussioncontrasting
confidence: 86%
“…The A. niger strains solubilized a high amount of insoluble phosphorus at 98.22 mg/L, followed by P. waksmanii at 95.77 mg/L, and P. brevicompactum at 74.63 mg/L. The values presented here exceed those highlighted in other studies [17,36,37,43,[47][48][49][50]; however, they were lower than the values presented for the Aspergillus sp. strain (167.7 mg/L) [37].…”
Section: Discussioncontrasting
confidence: 77%
“…In recent years various techniques for solubilization of insoluble RP and sparingly soluble organic and inorganic P sources have been proposed, with increasing emphasis on application of P‐solubilizing bacteria (PSBs) ( Hameeda et al, ; Panhwar et al, ; Selvakumar et al, ; Abbasi et al, ; Moreno Quevedo et al, ).The P solubilizing potential of these PSBs is due to their ability to produce and release acidic metabolites, such as organic acids, that through their hydroxyl and carboxyl groups chelate the cations bound to phosphate and then convert them into the soluble forms ( Khan et al, 2009). Therefore, the ability of PSBs to solubilize P complexes has been attributed to the process of acidification, chelation, exchange reactions, and production of organic acids ( Goldstein , ; Chen et al, ; Ekin , ).…”
Section: Introductionmentioning
confidence: 99%